2006
DOI: 10.1261/rna.2165806
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolo-C as a fluorescent probe for monitoring RNA secondary structure formation

Abstract: Pyrrolo-C (PC), or 3-[b-D-2-ribofuranosyl]-6-methylpyrrolo [2,3-d]pyrimidin-2(3H)-one, is a fluorescent analog of the nucleoside cytidine that retains its Watson-Crick base-pairing capacity with G. Due to its red-shifted absorbance, it can be selectively excited in the presence of natural nucleosides, making it a potential site-specific probe for RNA structure and dynamics. Similar to 2-aminopurine nucleoside, which base-pairs with uridine (or thymidine), PC's fluorescence becomes reversibly quenched upon base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 46 publications
1
86
0
Order By: Relevance
“…Ribonucleoside 2 was then converted into the corresponding 5′-triphosphate 2TP by a conventional method, 16 using freshly distilled POCl 3 and tributyl ammonium pyrophosphate. The triphosphate was extensively purified by ion exchange chromatography and HPLC, and thoroughly characterized using mass spectrometry as well as, 1 H, 13 C and 31 P NMR spectroscopy (see Experimental Section).…”
Section: Synthesis and Photophysical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ribonucleoside 2 was then converted into the corresponding 5′-triphosphate 2TP by a conventional method, 16 using freshly distilled POCl 3 and tributyl ammonium pyrophosphate. The triphosphate was extensively purified by ion exchange chromatography and HPLC, and thoroughly characterized using mass spectrometry as well as, 1 H, 13 C and 31 P NMR spectroscopy (see Experimental Section).…”
Section: Synthesis and Photophysical Propertiesmentioning
confidence: 99%
“…13 To rectify this general deficiency in fluorescent pyrimidine analogs, we have recently initiated a program in search for families of emissive and responsive nucleobase analogs. The basic requirement that are imposed upon the new nucleoside analogs include: (a) to maintain high structural similarity to the natural nucleobases, (b) to display emission at long wavelengths, preferably in the visible range, (c) to retain sufficient emission quantum efficiency to be utilized in real time fluorescence-based assays, and, importantly, (d) to possess sensitivity to the microenvironment that is manifested in markedly different photophysical parameters (emission wavelength λ em , quantum efficiency φ f and/or excited state lifetime τ) in aqueous versus apolar environment.…”
Section: Introductionmentioning
confidence: 99%
“…In the ground state, C3 forms one hydrogen bond with C17, which is stabilized by stacking interactions, while in the active state, C3 forms a Watson-Crick base pair with G8. Since it has previously been shown that base-pairing of pyC with guanosine strongly lowers its quantum yield (Tinsley and Walter 2006), the observed decrease indicates a transition from ground to active state. For the C1.1, the base-pairing with G2.1 occurs in both ground and active states; therefore, the expected overall amplitude of signal change is small and depends only on the transition between stacking interactions with C3 in the ground state to the stacking interaction with the G8-C3 base pair in the active state.…”
Section: Distinct Folding Of Catalytic Core and Auxiliary Structural mentioning
confidence: 81%
“…Here, we describe a fast kinetic folding analysis approach using the highly sensitive fluorescent cytosine analog pyrrolo-cytosine (pyC) (Berry et al 2004). pyC forms a Watson-Crick-like base pair with guanosine and was shown to maintain all structural and thermodynamic features of a standard guanosine-cytosine base pair (Dash et al 2004; Thompson and Miyake 2005;Tinsley and Walter 2006;Zhang and Wadkins 2009). Its incorporation at multiple positions in the extended hammerhead ribozyme was previously shown not to interfere with the function of the ribozyme (Lambert et al 2006).…”
Section: +mentioning
confidence: 99%
“…The PyC analog was previously shown to be an excellent probe for proteinnucleic acid interactions (Berry et al 2004;Tinsley and Walter 2006), because it can be selectively excited at 350 nm, well separated from the absorbance at 260 nm of natural nucleotides, and has an emission maximum of 460 nm, far removed from that of protein tryptophans (emission=340 nm). In addition, its fluorescence is sensitive to local conformational changes of nucleic acids, which has been exploited to study the dynamics and stabilities of DNA helices, RNA duplexes, and a DNA/RNA hybrid (Liu and Martin 2002;Tinsley and Walter 2006). Our method of fluorescent labeling of tRNA uses the CCA enzyme to incorporate PyC and generates fluorescent products that are substrates for aminoacylation.…”
Section: Introductionmentioning
confidence: 99%